If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 68 + 7x = 0 Solving 68 + 7x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-68' to each side of the equation. 68 + -68 + 7x = 0 + -68 Combine like terms: 68 + -68 = 0 0 + 7x = 0 + -68 7x = 0 + -68 Combine like terms: 0 + -68 = -68 7x = -68 Divide each side by '7'. x = -9.714285714 Simplifying x = -9.714285714
| 6-2c=2 | | p+33=16 | | 4x+7=-7-8x | | -4/-2 | | 30x+7=-7-8x | | 3x+7=-7-8x | | m/6+1/4(m+3)=1/3(m+7) | | 3+6x+15=-7x-2+3x | | x^3+2x^2=200 | | -11/3=-7/6k-2/3k | | 6x+5-4x=8-x+9 | | 2x-2.5=10 | | 25+5(y+20)=3(y-1) | | 4x-1/x=0 | | -24x^2+21x+15=0 | | 8(x-5)-6=26x-190 | | -16-4x=8x-7 | | 7x-8+3x=5x-13 | | -16-4x=8-7 | | -0.5x-5=0 | | 56x+9=89-5x | | 3/x+2=7 | | [9-2(4-1)]= | | 4y-3=6y+21 | | 3x+3-12=-5 | | 48/2^3+25*(9-7) | | c=2x+18 | | -7/2x+1+31/2=8 | | x^3-5x=14 | | -4+0.33x=0 | | 8(x-5)-6=26x-90 | | 2x-5=2x-35 |